miRNA Involvement in Cerebral Ischemia-Reperfusion Injury - Neag, Maria-Adriana; Mitre, Andrei-Otto; Burlacu, Codrin-Constantin; Inceu, Andreea-Ioana; Mihu, Carina; Melincovici, Carmen-Stanca; Bichescu, Marius; Buzoianu, Anca-Dana (Frontiers in Neuroscience, 2022)
Cerebral ischemia reperfusion injury is a debilitating medical condition, currently with only a limited amount of therapies aimed at protecting the cerebral parenchyma. Micro RNAs (miRNAs) are small, non-coding RNA molecules, which down regulate messenger RNAs, thereby modulating gene expression and cellular signaling through a various array of mechanisms and pathways. In neurological area, miRNAs have been evaluated as potential regulators in brain development processes and pathological events. Following ischemic hypoxic stress, the cellular and molecular events initiated dysregulate different miRNAs, responsible for long-terming progression and extension of neuronal damage. Taking the suppressive and limitative role of miRNAs in preventing the extension of neuronal damage, in the detriment of their deleterious effects, poses an emerging strategy for reducing the neurological burdens following an ischemic event. This review aims to summarize the recent literature evidence of the miRNAs involved in signaling and modulating cerebral ischemia-reperfusion injuries, thus pointing their potential in limiting neuronal damage and repair mechanisms. An in-depth overview of the molecular pathways involved in ischemia reperfusion injury and the involvement of specific miRNAs, could provide future perspectives in the development of neuroprotective agents targeting these specific miRNAs.